Hepatocellular carcinoma patients with undetectable baseline hepatitis B viral DNA may benefit from immunotherapy - Yan Jian; Sicong Jiang; Zhimin Qiu; Meijian Wang; Hanzhi Dong; Lin Zhou; Yu-an Qiu (BMC Gastroenterology)
Abstract Background The relationship between hepatitis B virus (HBV) load and the survival or safety of immunotherapy in patients with advanced hepatocellular carcinoma (HCC) remains ambiguous. Methods A multicenter study involving patients with advanced HCC who are treated with anti-PD-1 immunotherapy and entecavir from December 2019 to 2023 was conducted. Patients were categorized based on HBV-DNA levels to evaluate correlations with progression-free survival (PFS), overall survival (OS), and adverse events. Results A total of 162 patients participated in the study. Among HCC patients with a positive hepatitis B surface antigen (HBsAg), median PFS was not significantly better for patients with HBV-DNA levels ≤ 2000 IU/ml compared to levels > 2000 IU/ml (4.60 months vs. 3.90 months, p = 0.17). Similarly, median OS did not differ between the two groups (10.53 months vs. 8.17 months, p = 0.14). Patients with undetectable baseline HBV-DNA had better PFS than those detectable (5.03 months vs. 3.70 months, p = 0.03), but there was no significant difference in OS (11.80 months vs. 8.00 months, p = 0.10). Furthermore, the incidence of hepatic impairment was not correlated with the baseline HBV - DNA load (6.1% vs. 7.9%, p > 0.05). Conclusions The status of HBV DNA exerts an influence on the prognosis of HCC patients undergoing immunotherapy, and this influence is independent of the viral load. HCC patients with undetectable HBV DNA tend to have more favorable short - term survival outcomes. For patients who have received effective antiviral therapy, elevated levels of HBV DNA should not be used as an exclusion criterion for immunotherapy.